In vitro comparison of two food choice methodologies for necrophagous species of the genus Thanatophilus (Coleoptera: Staphylinidae: Silphinae) - Kadlec, Jakub; Jakubec, Pavel; Šípek, Petr (Journal of medical entomology, 2024)
To accurately model the food webs, we need to acquire precise data on food ecology of the interacting species. This allows better understanding of the trophic interactions and for the necrophagous species this information could be used in medico-legal investigations. For this reason, we recently proposed standardized laboratory methodology to assess the foraging strategies based on parallel testing of 2 food items (meat, dead larvae) (Jakubec et al. 2021). The original methodology had 2 shortcomings. It was not suited for testing living larvae, which could prove predatory behavior of the species. The methodology was also based on parallel experimental design, where the food items are tested together, which could underestimate the maximum consumption of the tested subject for some items. To test if these concerns are valid, we improved original methodology allowing testing living larvae as well as a new sequential experimental setup, where consumption of each item is tested individually in a random order, thus theoretically giving an unbiased maximum consumption estimate. These methodologies were tested head-to-head on 3 forensically relevant species from the genus Thanatophilus (Thanatophilus micans (Fabricius 1794)(Fabricius 1794), Thanatophilus rugosus (Linnaeus, 1758), and Thanatophilus sinuatus(Fabricius, 1775)). The experiments have confirmed that all 3 species are almost strictly necrophagous, although they were capable of predation, despite the presence of preferred food (meat). The comparison also showed that the sequential design has indeed improved capability to quantify the maximal consumption of the given food item. Thus, we suggest following this methodology in future studies.
Keywords: stravovací zvyklosti; Forensic Entomology; Food Chain; Food Preferences; larva; forensic entomology; zvířata; preference v jídle; behavior; Silphinae; Coleoptera; forenzní entomologie; brouci; food choice; Larva; Animals; Feeding Behavior; necrophagy; potravní řetězec